A Review on Direct Power Control for Applications to Grid Connected PWM Converters - Trivedi, T. A.; Jadeja, R.; Bhatt, P. (Engineering, Technology & Applied Science Research, 2015)
The Direct Power Control strategy has become popular as an alternative to the conventional vector oriented control strategy for grid connected PWM converters. In this paper, Direct Power Control as applied to various applications of grid connected converters is reviewed. The Direct Power Control for PWM rectifiers, Grid Connected DC/AC inverters applications such as renewable energy sources interface, Active Power Filters, Doubly Fed Induction Generators and AC-DC-AC converters are discussed. Control strategies such as Look-Up table based control, predictive control, Virtual Flux DPC, Model based DPC and DPC-Space Vector Modulation are critically reviewed. The effects of various key parameters such as selection of switching vector, sampling time, hysteresis band and grid interfacing on performance of direct power controlled converters are presented.